Efeitos da exposição subcrônica à sibutramina sobre parâmetros reprodutivos e fertilidade de ratos machos wistar adultos - Missassi, Gabriela [UNESP] (Universidade Estadual Paulista (Unesp), 2016)
Sibutramine is a non-selective serotonin-norepinephrine reuptake inhibitor largely used for weight loss. In a previous work, we showed the pharmacological mechanisms involved in the reduction on sperm quality and fertility of rats exposed to this anorexigen in the light phase of light-dark (l/d) cycle. Considering that rodents are nightlife animals, with higher metabolic activity during the dark phase, the present work aimed to further investigate whether the alterations found in rat sperm quality would be maintained after treatment in this period. For this, adult male Wistar rats were treated with sibutramine (10 mg/kg/day) or vehicle for 15 days in the dark phase of the light-dark cycle. Sibutramine decreased final body and reproductive organ weights, as well as the testosterone levels and number of sperm with progressive motility. These animals also had an acceleration in the sperm transit time in the epididymis and a decrease in sperm concentrations throughout this organ (histopathological analysis). In conclusion, the impairment of reproductive parameters were enhanced when the exposure occurred during the dark phase of the l/d cycle, which corresponds to more active period of these animals.

Não disponível
Effects of subchronic exposure to sibutramine on reproductive parameters and fertility of wistar adult male rats
Keywords: Toxicidade - Testes; Epidídimo; Sibutramina; Drogas - Efeito fisiológico; Sêmen; Rato como animal de laboratorio; Epididymis